The Effect of Product Image and Website Quality on the E-Purchase Decision through Website Experience - Hernandi Sujono; Ratih Hurriyati; Lili Adi Wibowo; Heny Hendrayati (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
In the globalization era or the 4.0 era, all activities that used to be done offline can now be completed online using the internet network. Likewise with buying and selling activities, openness, and Internet connectivity, with online media, one of which is the website. Therefore, the research objectives are to analyze the effect of the product image and website quality on online purchasing decisions; the impact of the product image and website quality on user experience (web experience); the effect of user experience (web experience) on online purchasing decisions at a Parfume Online Store. This research is a quantitative study, an inferential statistical study that takes a certain number of samples to explain the population. By collaborating with the Parfume Online Store for data collection, it is targeted that at least 100 responses are collected from online questionnaires and analyzed by structural equation modeling with Partial Least Square (PLS) software used as a tool to assist procedures. After all, the conclusions of this study are: 1) Product Image's significant positive effect on E-Purchase Decision, 2) Product Image's significant positive effect on Web Experience, 3) Web Experience's significant positive effect on E-Purchase Decision, 4) Web Quality's significant positive effect on E- Purchase Decision, 5) Web Quality's significant positive effect on Web Experience, 6) Product Image's significant positive effect on E-Purchase Decision, 7) Web Quality's significant positive effect on E-Purchase Decision Variables.